2017
DOI: 10.1073/pnas.1705367114
|View full text |Cite
|
Sign up to set email alerts
|

PrimPol is required for replication reinitiation after mtDNA damage

Abstract: Eukaryotic PrimPol is a recently discovered DNA-dependent DNA primase and translesion synthesis DNA polymerase found in the nucleus and mitochondria. Although PrimPol has been shown to be required for repriming of stalled replication forks in the nucleus, its role in mitochondria has remained unresolved. Here we demonstrate in vivo and in vitro that PrimPol can reinitiate stalled mtDNA replication and can prime mtDNA replication from nonconventional origins. Our results not only help in the understanding of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
88
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 58 publications
(69 reference statements)
9
88
0
Order By: Relevance
“…1G). This may suggest changes in the mode of replication or initiation as this region contains the origins of replication and transcription, similar to a previous study on PrimPol -/-MEFs that showed replication changes in this region (24).…”
Section: Primpol -/Cells Have a Defect In Mitochondrial Dna Proliferasupporting
confidence: 88%
See 3 more Smart Citations
“…1G). This may suggest changes in the mode of replication or initiation as this region contains the origins of replication and transcription, similar to a previous study on PrimPol -/-MEFs that showed replication changes in this region (24).…”
Section: Primpol -/Cells Have a Defect In Mitochondrial Dna Proliferasupporting
confidence: 88%
“…In addition, we also found a similar increase (~ 51%) in mtDNA copy number in DT40 PrimPol -/cells, which could be complemented by the addition of the WT protein ( Fig. S3B), whilst similar increases have also been reported in MEFs (24). Upon staining these cells with an anti-DNA antibody, we found a clear increase in mtDNA nucleoid number but no increase in nucleoid size (Fig.…”
Section: Primpol -/Cells Have a Defect In Mitochondrial Dna Proliferasupporting
confidence: 82%
See 2 more Smart Citations
“…Among various TLS polymerases, the primase/polymerase PrimPol has been shown to help both in nuclear and mitochondrial DNA replication fork progression (7-8). Additionally, PrimPol can also re-prime downstream of blocking lesions, thus re-reinitiating DNA replication (1,(9)(10)(11)(12)(13)(14)(15).PrimPol is a monomeric enzyme belonging to the archaeal-eukaryotic primase (AEP) superfamily (16). Its catalytic core contains three highly conserved motifs (see Figure1A) which build the dNTP binding site used for elongation (17).…”
mentioning
confidence: 99%